Pengujian Aplikasi Homestay Kosasih: Analisis Fungsionalitas Dan Penerimaan Pengguna Menggunakan Metode Black Box Dan UAT - Nurvalentini, Dewi; Umam, Khoirul; Hakim, Lukman; Febrita, Ruth Ema; Prasetyo, Junaedi Adi (Jurnal Informatika dan Komputer, 2024)
The research focuses on evaluating the functionality of the Homestay Kosasih application, particularly in terms of user interaction, data management, and user satisfaction. This study combines Black box Testing and UAT methods to provide a comprehensive understanding of the application's quality and performance. The research aims to assess the application's functional features, focusing on user interface, ease of use, and the application's ability to meet user expectations. Through analysis, this study will provide a thorough understanding of the application's quality and also measure the level of user satisfaction with the hotel reservation application, involving assessments of user interface, ease of use, and the application's success in meeting user expectations. The results show that the Homestay Kosasih application exhibits good functionality with 80.9% valid test cases and good user acceptance with an average score of 74.39% from 40 respondents. Therefore, it can be concluded that the entire series of application testing for Homestay Kosasih is deemed good.